2013
DOI: 10.1159/000355370
|View full text |Cite
|
Sign up to set email alerts
|

Visual Eyes: A Quantitative Analysis of the Photoreceptor Layer in Deep-Sea Sharks

Abstract: The marine environment presents unique visual challenges for a range of organisms, particularly those dwelling at great depths, where sunlight may either be absent or drop to very low levels. Under these environmental conditions, the visual system must maximise light absorption in order to enhance the detection of prey, predators and potential mates. Using stereological analysis of retinal wholemounts, the distribution and number of photoreceptors (rods) was determined for 5 deep-sea shark species from a range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…The harvesting and use of this specimen was approved by the University of the Witwatersrand Animal Ethics Committee (2008/36/1) and the University of Western Australia Ethics Committee (RA/3/100/927). Because other studies in many vertebrate species have shown that interindividual variation in the total number and topographic distribution of both photoreceptors and retinal ganglion cells is generally low [Lisney et al, 2012;Coimbra et al, 2013;Lisney et al, 2013a, b;Newman et al, 2013;Coimbra et al, 2014a, b;de Busserolles et al, 2014a, b;Coimbra et al, 2015], the eyes from this single specimen of Ansorge's cusimanse can be considered representative for the characterization of the retinal topographic specializations in this species. In addition, given the overall lack of information about the biology of Ansorge's cusimanses, we found it important to study the retinal topographic specializations in this species to predict the importance of vision in the use of habitat and behavior.…”
Section: Specimenmentioning
confidence: 81%
“…The harvesting and use of this specimen was approved by the University of the Witwatersrand Animal Ethics Committee (2008/36/1) and the University of Western Australia Ethics Committee (RA/3/100/927). Because other studies in many vertebrate species have shown that interindividual variation in the total number and topographic distribution of both photoreceptors and retinal ganglion cells is generally low [Lisney et al, 2012;Coimbra et al, 2013;Lisney et al, 2013a, b;Newman et al, 2013;Coimbra et al, 2014a, b;de Busserolles et al, 2014a, b;Coimbra et al, 2015], the eyes from this single specimen of Ansorge's cusimanse can be considered representative for the characterization of the retinal topographic specializations in this species. In addition, given the overall lack of information about the biology of Ansorge's cusimanses, we found it important to study the retinal topographic specializations in this species to predict the importance of vision in the use of habitat and behavior.…”
Section: Specimenmentioning
confidence: 81%
“…In the 19th century, retinal topography maps were mentioned by von Graefe (1865, p. 22, ''Netzhautkarte'') and, to our best knowledge, were formally introduced by Stone (1965). Retinal topography maps have since been widely used, with many recent publications (e.g., Ahnelt, Schubert, Kübber-Heiss, Schiviz, & Anger, 2006;Coimbra, Nolan, Collin, & Hart, 2012;Coimbra, Collin, & Hart, 2013, 2014a, 2014bLandgren, Fritsches, Brill, & Warrant, 2014;Lisney, T. J., Stecyk, K., Kolominsky, J., Graves et al, 2013;Lisney, T. J., Stecyk, K., Kolominsky, J., Schmidt et al, 2013;Moore, Doppler, Young, & Fernandez-Juricic, 2013;Newman, Marshall, & Collin, 2013;Schiviz, Ruf, Kuebber-Heiss, Schubert, & Ahnelt, 2008;Ullmann et al, 2012). Comparative analyses over the last few decades have yielded maps for several hundred vertebrates, many of which (approx.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have thus far concentrated on the distribution of retinal ganglion cells based on their large size and accessibility. However, where photoreceptors have been stereologically sampled, similar patterns have been revealed, that is, in the ornate wobbegong, Orectolobus ornatus; the whitetip reef shark, Triaenodon obesus; the epaulette shark, Hemiscyllium ocellatum; the sandbar shark, Carcharhinus plumbeus; and six species of deep‐dwelling sharks …”
Section: Photoreceptionmentioning
confidence: 81%
“…However, in some species where the head is dorso‐ventrally flattened, that is, in the Sphyrnidae family of hammerhead sharks, the eyes are elongated rostro‐caudally, with a greater equatorial eye diameter than axial eye diameter. Absolute eye size varies from over 62 mm in the pelagic, big‐eyed thresher shark ( Alopias superciliosus) to less than 3 mm in the deep‐sea, longsnout dogfish ( Deania quadrispinosum ) . Oceanic and shallow benthopelagic species, which predate on active, mobile prey, typically possess larger eyes than coastal benthic sharks when body size is taken into account .…”
Section: Eye Shape and Sizementioning
confidence: 99%
See 1 more Smart Citation